PERAN AKTIF HAKIM DALAM PEMERIKSAAN KETERANGAN SAKSI DALAM PERSIDANGAN : MENUJU HAKIM YANG PROFESIONAL PADA ERA KEMAJUAN TEKNOLOGI INFORMASI - Uswatul Fikriyah (Al'Adalah, 2019)
In civil cases in Religious Courts, especially divorce cases, the witnesses evidence is a matter that is always presented by the parties. Judges must have professional methods and abilities to explore legal facts and produce quality decisions, the development of information technology that was responded to by the Supreme Court made all proceedings carried out through electronic media. This paper discusses how the duties and the roles of Judges in examining the Witness' statements to become Professional Judges in the era of advancement in information technology. The results of this study: a judge in deciding a case through several stages consisting of Constantine, Qualifiers, and Constituencies. In each stage, the Judge must have a sensitivity of conscience, moral intelligence and hone professionalism. The professionalism of judges must refer to Point 10 of the ethics code and guidelines for judge behaviour. The professionalism of a judge is interpreted as a moral attitude based on a determination to carry out the task seriously supported by expertise, skills, and broad insight. In addition, the Judge must be guided by the concept of Islamic professionalism, which is seen as synchronization between human movements in two forms, namely spiritual and physical.